2006
DOI: 10.1016/j.ab.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Formation of fluorescent proteins by the attachment of phycoerythrobilin to R-phycoerythrin alpha and beta apo-subunits

Abstract: Formation of fluorescent proteins was explored after incubation of recombinant apo-subunits of phycobiliprotein R-phycoerythrin with phycoerythrobilin chromophore. Alpha and beta apo-subunit genes of R-phycoerythrin from red algae Polisiphonia boldii were cloned in plasmids pET-21d (+). Hexa-histidine tagged apo-alpha and apo-beta subunits were expressed in Escherichia coli. Although expressed apo-subunits formed inclusion bodies, fluorescent holo-subunits were constituted after incubation of Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…¶ An increasing number of lyases has recently been identified that catalyze the chromophore addition and are specific not only for the chromophore but also for the apoprotein and the binding site (12)(13)(14)(15)(16). Based on the capacity of several of the respective apoproteins to also bind the chromophores autocatalytically (17)(18)(19)(20)(21), a chaperone-like function has been suggested (12). It enhances and guides the autocatalytic binding, which is generally of low fidelity, possibly by conformational control of the chromophore (18).…”
mentioning
confidence: 99%
“…¶ An increasing number of lyases has recently been identified that catalyze the chromophore addition and are specific not only for the chromophore but also for the apoprotein and the binding site (12)(13)(14)(15)(16). Based on the capacity of several of the respective apoproteins to also bind the chromophores autocatalytically (17)(18)(19)(20)(21), a chaperone-like function has been suggested (12). It enhances and guides the autocatalytic binding, which is generally of low fidelity, possibly by conformational control of the chromophore (18).…”
mentioning
confidence: 99%
“…20世纪90年代, Kahn等人 [56] 发现裂合酶CpeY和 CpeZ可能会催化PE的α及β亚基与PEB共价结合. 2006 年, Isailovic等人 [57] [59] . 2002年, 美 国加州大学的Glazer研究组 [60] 进行了holo-PecA在大 [62,63] .…”
Section: 年份 研究者 研究成果unclassified
“…在藻红蛋白方面, 针对脱辅基 PE 和亚基结合 PEB 的研究还只是处于初步阶段 [29,30] , 色基 PUB 或 PVB 与脱辅基蛋白如何结合的研究还没有进展. 结合 PCB 的 holo-PC 亚基, 是 Glazer 研究组 [31] 在 E. coli 体内通过 PAT 和 PCB 两个载体, 成功表达 了包含 cpcE/F 裂合酶在内的 5 个基因, 并通过 His 6 标签纯化得到的.…”
Section: 三聚体的研究背景unclassified